CP-080 Analysis of ondansetron prescription practices in the care of postoperative nausea and vomiting. (24th February 2014) - Imbert, C; Martin, L; Delette, A; Welti, C; Hoang-Nguyen, DT; Barreteau, H; Oliary, J
Abstract : Background: In 2013, the French Agency for Medicines and Health Products Safety (ANSM) issued recommendations for the use of ondansetron in the context of chemotherapy-induced nausea and vomiting (CINV). They focus on a reduction of maximum intravenous dose per injection due to a dose-dependent QT prolongation. The use of ondansetron in postoperative nausea and vomiting (PONV) is not concerned with these recommendations as recommended doses are lower: 4 mg intravenous (IV) in a single dose. We would like to know the actual doses of ondansetron used in PONV in our hospital. Purpose: To analyse ondansetron prescription practices in the management of PONV and the compliance with the dosage recommendations. Materials and methods: Ondansetron prescription practices were analysed retrospectively over a 2 month period (June and July 2013). The following data were provided by the computer-assisted prescription software: route of administration, dose per day (dose per administration, frequency), treatment duration, prescribing care unit, prescribing care unit type (medical or surgical). Results: 263 ondansetron prescriptions (for 223 patients) were obtained by our software. 85% (n = 224) of prescriptions come from surgical care units. IV and oral (PO) routes respectively represent 60% (n = 158) and 40% (n = 105) of prescriptions. The average treatment duration is 5 days and only 12% (n = 31) of prescriptions include a single administration as recommended. Prescribed IV doses are higher than 4 mg per day in 86% (n = 136) of the cases and can reach 32 mg per day (n = 2); PO prescribed doses are higher than 16 mg per day in 80% (n = 84) of the cases with a maximum dose of 24 mg per day (n = 84). 46% (n = 121) of prescriptions are conditional ('if necessary') (41% IV and 53% PO). The majority of prescribed daily doses are higher than recommended doses and reach the recommended doses in CINV (16 mg per day PO and 8 to 32 mg per day IV). Conclusions: The doses of ondansetron used in PONV are much higher than marketing authorisation recommended doses. Recommendations about the risk of QT prolongation should not be limited to the use of ondansetron in CINV, it seems necessary to make recommendations in the care of PONV. No conflict of interest.